Online Buying and Selling Transactions during The Covid-19 Pandemic - Yuliana, Rr. Retno Rizki Dini; Adityawati, Septian (Universitas Prasetiya Mulya, 2022)
The Covid-19 pandemic that has hit the whole world since the end of 2019 has limited community activities, including economic transactions. This study aims to analyze the impact of Covid-19 on the behavior of Indonesian people. It also explained online purchases and sales and the implications of these changes. This study used quantitative descriptive analysis with data collection through online surveys. The results showed that online purchases increased significantly, the majorities are health products and ready-to-eat foods. Many MSMEs felt a positive impact, where new businesses have sprung up to respond to high demand. Some respondents have just started a business during Covid-19 and started trying to sell their products online.